2013
DOI: 10.1111/wrr.12022
|View full text |Cite
|
Sign up to set email alerts
|

Mannose reduces hyaluronan and leukocytes in wound granulation tissue and inhibits migration and hyaluronan‐dependent monocyte binding

Abstract: Wound healing is a highly regulated process starting from coagulation and ending in tissue remodeling. The end result varies from perfectly restored tissue, such as in early fetal skin, to scars in adults. The balanced repair process is frequently disturbed by local or systemic factors, like infections and diabetes. A rapid increase of hyaluronan is an inherent feature of wounds and is associated with tissue swelling, epithelial and mesenchymal cell migration and proliferation, and induction of cytokine signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In the present work, we studied whether IL-1␤ exerts a similar effect in keratinocytes and how this CD44 is associated with the formation of the cytokine-induced, extended hyaluronan coats observed previously in these cells (26,33). Our data show that besides slightly increasing CD44 expression, IL-1␤ blocked phosphorylation of CD44 at serine 325 while at the same time it increased CD44 homomeric complexes and binding of CD44 to ezrin.…”
mentioning
confidence: 62%
“…In the present work, we studied whether IL-1␤ exerts a similar effect in keratinocytes and how this CD44 is associated with the formation of the cytokine-induced, extended hyaluronan coats observed previously in these cells (26,33). Our data show that besides slightly increasing CD44 expression, IL-1␤ blocked phosphorylation of CD44 at serine 325 while at the same time it increased CD44 homomeric complexes and binding of CD44 to ezrin.…”
mentioning
confidence: 62%
“…Several growth factors and cytokines induce HAS expression and increase HA synthesis in inflamed tissues, and the accumulated HA modulates cellular inflammatory responses . It has been shown that inhibition of HA synthesis reduces tissue accumulation of leukocytes, including macrophages . In a murine mammary tumour model with conditional knockout of HAS2 in stromal fibroblasts, macrophage migration into the HA‐deficient tumour stroma was also severely impaired, blocking tumour angiogenesis and lymphangiogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been shown that inhibition of HA synthesis reduces tissue accumulation of leukocytes, including macrophages. 26 In a murine mammary tumour model with conditional knockout of HAS2 in stromal fibroblasts, macrophage migration into the HA-deficient tumour stroma was also severely impaired, blocking tumour angiogenesis and lymphangiogenesis. 22 In agreement with the above results, we found a strong correlation between TAMs, HA, and HASs, suggesting that the increased HAS expression and accumulation of HA also facilitate macrophage infiltration during human breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mannose at ~20 mM concentration inhibits HA synthesis by causing a reduction in the cellular concentration of UDP- N -acetylhexosamines (i.e., UDP- N -acetyl-D-glucosamine and UDP- N -acety-D-galactosamine). Mannose treatment was shown to inhibit dermal fibroblast invasion and to prevent enhanced leukocyte binding to HA (Jokela et al, 2008, 2013). However, antitumor effects of mannose in the context of HA synthesis inhibition have not yet been investigated.…”
Section: Targeting Ha Productionmentioning
confidence: 99%